ANTIBACTERIAL ACTIVITY OF BIFIDOBACTERIA ISOLATED FROM INFANT FAECES - E, Bayar; Sh, Demberel; Ishii, Satomi; Miyazaki, Kensuke; Yoshida, Takashi (Proceedings of the Mongolian Academy of Sciences, 2018)
Antibacterial activity of bifidobacteria isolated from Mongolian infant faeces was elucidated on pathogenic intestinal bacteria for the development of a new antibacterial bifidobacteria, the permission for which was granted by the Mongolian Medical Ethics Committee Approval (MMECA). A total of forty-nine single colonies were obtained from 3 samples by using a BL medium enrichment. Among them, 29 isolates had Gram−positive, catalase−negative properties, and maul−like or Y−shaped morphology, and then, 20 Bifidobacterium breve and 9 Bifidobacterium longum strains were detected by the B. breve and B. longum specific primers. Organic acids produced by the isolated bifidobacteria in their cell-free supernatants were quantitatively analyzed by a spectrophotometric absorbance at 340 nm, suggesting that D−lactic, L−lactic, and acetic acids were produced, and the pH of the supernatants was at 3.86−4.55. The isolated bifidobacteria showed antibacterial activity toward Escherichia coli and Salmonella typhimurium as high as that of a standard bifidobacteria, however, lower activity against Staphylococcus aureus. The antibacterial activity was probably due to the production of organic acids.